Micromilling of tungsten carbide using focused ion beam - Ali, Mohammad Yeakub; Ong, A. S.; Konneh, Mohamed (2005)
This paper describes the effect of focused ion beam (FIB) micromilling parameters on tungsten carbide for the fabrication of any microcomponents. The FIB parameters such as aperture size, ion dose, dwell time, etc. were investigated in this study. A series of experiments were conducted on tungsten carbide with varying operating parameters to establish the correlation how the parameters affect the micromilling process and quality of the final component. All the experiments were carried out with dry micromilling using serpentine scanning mode. Empirical models were formulated to predict the sputtered depth which increased with higher ion dose significantly but the relationship was nonlinear. Some of the experimental results are discussed with qualitative judgement as it was difficult to explain quantitatively.